Transformation of the Labor Political Movement: Confronting the Injustices of Labor Policy in Indonesia - Qolbi, Yahdi; Patty, Alberto Noviano; Jefri; Jamaludin, Hamzah (JPP (Jurnal Politik Profetik), 2024)
The injustice of labor policy in Indonesia has marginalized workers in the tripartite negotiation process dominated by the logic of corporatism, reflected in the policies of the Job Creation Law, Government Regulation Number 78 of 2015 regarding wages and several labor rules tend to favor employers and ignore the needs of a decent living for workers. The research aims to analyze the driving factors of resistance, the form of movement transformation, and its political implications. The qualitative descriptive method uses primary data from some government regulations on labor in Indonesia, secondary data from online news (2014–2024), journal articles, and data from relevant institutions related to the labor movement. Based on the theory of resource mobilization and the transformation of the labor movement from street demonstrations to the structural political strategy of the Labor Party's representation, it shows the expansion of influence and connectivity. The study results show that the labor political movement faces severe challenges, such as the dominance of the power of capital owners and fluctuations in support at the electoral level. However, amid these dynamics, the labor movement has succeeded in building a strategic foundation to influence policies and fight for workers' welfare in a more organized and systematic.